2002
DOI: 10.1017/s1366728902000147
|View full text |Cite
|
Sign up to set email alerts
|

Making a minimalist approach to codeswitching work: Adding the Matrix Language

Abstract: In this paper, we show how some proposals within the Minimalist Program are compatible with a model of codeswitching that recognizes an asymmetry between the participating languages, the Matrix Language Frame model. Through our discussion of an analysis of NPs in a Spanish–English corpus, we illustrate this compatibility and show how recent minimalist proposals can explain the distribution of nouns and determiners in this data set if they adopt the notion of Matrix Language as the bilingual instantiation of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
4
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 13 publications
11
118
4
3
Order By: Relevance
“…For example, Liceras et al reported, from their review of research on mixed Spanish-English DPs in spontaneous adult speech and their own study of child speech, that mixed DPs with Spanish determiners are far more frequent than with English determiners [6]. In their own study of child speech, only about 5% of the mixed DPs had English determiners; in adult speech, Jake et al found 161 instances of Spanish determiners followed by English nouns, but no examples of English determiners followed by Spanish nouns [7]. However, Liceras et al [6] do not provide information about the morphosyntactic frame in which the mixed DPs appeared, which Herring et al [8] found to be relevant, as will be described below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Liceras et al reported, from their review of research on mixed Spanish-English DPs in spontaneous adult speech and their own study of child speech, that mixed DPs with Spanish determiners are far more frequent than with English determiners [6]. In their own study of child speech, only about 5% of the mixed DPs had English determiners; in adult speech, Jake et al found 161 instances of Spanish determiners followed by English nouns, but no examples of English determiners followed by Spanish nouns [7]. However, Liceras et al [6] do not provide information about the morphosyntactic frame in which the mixed DPs appeared, which Herring et al [8] found to be relevant, as will be described below.…”
Section: Introductionmentioning
confidence: 99%
“…They state that "If Spanish is the ML in any CS corpus, then it is likely Spanish determiners will dominate for this reason alone under an analysis based on the MLF model" [10] (p. 356). This prediction had already been captured in the 'Bilingual NP Hypothesis' proposed by Jake et al [7] and was motivated by the Uniform Structure Principle according to which the "structures of the matrix language are always preferred" [11] (p. 8).…”
Section: Introductionmentioning
confidence: 99%
“…"I think it has just …" (Pfaff, 1979, p. Jake et al (2002Jake et al ( , 2005, Myers-Scotton (2002) and Wei (2015).…”
Section: The Minimalist Modelmentioning
confidence: 99%
“…The constraints relevant to the present study are summarized in Dussias (2003), Lipski (1982Lipski ( , 1985, and Toribio (2001aToribio ( , 2001b. MacSwan (1999MacSwan ( , 2000MacSwan ( , 2004MacSwan ( , 2005 provides refinements based on the Minimalist paradigm, while Myers-Scotton (2002) and Jake, Myers-Scotton, and Gross (2002) analyze codeswitching from within the Matrix Language Framework. Most of the examples analyzed in the present study would receive similar acceptability judgments in all of the aforementioned theoretical frameworks.…”
Section: 1mentioning
confidence: 99%